The nitrone compound OKN-007 delays motor neuron loss and disease progression in the G93A mouse model of amyotrophic lateral sclerosis - Bhaskaran, Shylesh; Piekarz, Katarzyna M.; Brown, Jacob; Yang, Brian; Ocañas, Sarah R.; Wren, Jonathan D.; Georgescu, Constantin; Bottoms, Christopher; Murphy, Ashley; Thomason, Jessica; Saunders, Debra; Smith, Nataliya; et al. (Frontiers in Neuroscience, 2024)
Our study investigated the therapeutic potential of OKN-007 in the SOD1 G93A mouse model of amyotrophic lateral sclerosis (ALS). The impact of OKN-007, known for its antioxidant, anti-inflammatory, and neuroprotective properties, was tested at two doses (150 mg/kg and 300 mg/kg) at onset and late-stage disease. Results demonstrated a significant delay in disease progression at both doses, with treated mice showing a slower advance to early disease stages compared to untreated controls. Motor neuron counts in the lumbar spinal cord were notably higher in OKN-007 treated mice at the time of disease onset, suggesting neuroprotection. Additionally, OKN-007 reduced microglial activation and preserved reduced neuromuscular junction fragmentation, although it did not significantly alter the increase in astrocyte number or the decline in hindlimb muscle mass. MR spectroscopy (MRS) revealed improved spinal cord perfusion and normalized myo-inositol levels in treated mice, supporting reduced neuroinflammation. While the expression of several proteins associated with inflammation is increased in spinal cord extracts from G93A mice, OKN-007 dampened the expression of IL-1β, IL-1ra and IL-1α. Despite its promising effects on early-stage disease progression, in general, the beneficial effects of OKN-007 diminished over longer treatment durations. Further, we found no improvement in muscle atrophy or weakness phenotypes in OKN-007 treated G93A mice, and no effect on mitochondrial function or lifespan. Overall, our findings suggest that OKN-007 holds potential as a disease-modifying treatment for ALS, although further research is needed to optimize dosing regimens and understand its long-term effects.